Heretics and colonizers : forging Russia's empire in the south Caucasus - Breyfogle, Nicholas B., 1968- (Cornell University Press, 2005)
"In Heretics and Colonizers, Nicholas B. Breyfogle explores the dynamic intersection of Russian borderland colonization and popular religious culture. He reconstructs the story of the religious sectarians (Dukhobors, Molokans, and Subbotniks) who settled, either voluntarily or by force, in the newly conquered lands of Transcaucasia in the nineteenth century. By ordering this migration in 1830, Nicholas I attempted at once to cleanse Russian Orthodoxy of heresies and to populate the newly annexed lands with ethnic Slavs who would shoulder the burden of imperial construction."--Jacket